PEDAGOGICAL AND PSYCHOLOGICAL CHARACTERISTICS OF SOCIAL INTELLECT DEVELOPMENT IN FUTURE TEACHERS - Najmiddinova Saodat Abduvohid qizi (Proximus Journal Publishing, 2024)
This article talks about the specific features of the formation of social intelligence in future teachers. Also, the specific features of achieving educational achievements based on the formation of positive motivation for students' educational activities are revealed. In the course of education, theoretical and practical opinions about educational motives were expressed.
Keywords: intelligence; social intelligence; intensive; component